Determinan Kinerja Keuangan Sektor Kesehatan - Majidah, Majidah; Mutiara, Mutiara (Universitas Muhammadiyah Metro, 2024)
The company's goal in carrying out its business activities is to obtain optimal profits in order to provide value to shareholders and other stakeholders. This study aims to examine the effect of corporate governance disclosure, intellectual capital, value added capital employed, value added human capital and structured capital value added on financial performance. The object of this research is health sector companies listed on the IDX for the 2017-2021 period. With purposive sampling, 13 companies or 65 observations were obtained. Panel data regression with eviews 12 software was used to analyze the research data. The results showed that only corporate governance disclosure had a positive effect. The findings of this research indicate that health sector companies are relatively less innovative because their average intellectual capital is relatively diverse. The limitations of this study are shown by an adjusted r square of 14.39%; therefore, it is advisable to explore factors that have the potential to effect financial performance in future studies. Advice for companies to innovate operating activities to improve financial performance and maintain business continuity. The results of this study can also be considered by investors as important information for investment decisions.